Dampak Non Performing Loan Terhadap Peningkatan Pendapatan Perusahaan di Sektor Jasa Perbankan - Widyatmoko, Widyatmoko; Mahmud, Wildan; Hidajat, Moch. Sjamsul; Wahyu Putri, Stevani Tri (STAI Denpasar Bali, 2023)
It is hoped that the results of this research can be used as input and consideration for companies in making decisions and establishing policies to overcome problems related to the level of Non-Performing Loans of banks, especially Rural Banks. The population of this research are customers who use credit services who have experienced problems, especially in the non-performing loan category. The research uses quantitative research methods with analysis using the SPSS application and using multiple regression analysis techniques. In this research, the results can prove that the results of Non-Performing Loans will influence the increase in income. The results of the t-test analysis = 3.578 means that the hypothesis can be accepted, because the t-test > tcount. namely 3.578 > 3.078, meaning there is a correlation between the Non-Performing Loan variable and an increase in company income. Keywords: non-performing loans, increasing income, banking